ChemInform Abstract: MIDA—Vinylsilanes: Selective Cross‐Couplings and Applications to the Synthesis of Functionalized Stilbenes. Issue 21 (May 2015) - McLaughlin, Mark G.; McAdam, Catherine A.; Cook, Matthew J.
Abstract The Suzuki—Miyaura cross‐coupling of MIDA—boronates (III) with aryl halides (IV) followed by a Hiyama cross‐coupling of intermediate silanes with iodides (V) leads to desired stilbenes (VI) in moderate to high yields.